Behcet's disease, vascular complication in a young woman: Case report (Research, Society and Development, 2022)
Objectives: Behcet's disease (BD) is a chronic systemic inflammatory vasculitis of unknown etiology and systemic involvement characterized by recurrent oral and genital ulcerations, cutaneous manifestations and ocular, intestinal, neurological and vascular involvement. The aim of the study is to describe the clinical case of a patient diagnosed with Behcet's Disease who is admitted to the General Hospital of Fortaleza (HGF). Methods: Descriptive study of the case report type, using information obtained through interaction with the patient during hospitalization, as well as data obtained from the medical record of the results of laboratory tests and images. Discussion: Mucocutaneous lesions are the hallmark of the disease. Studies indicate that clinical manifestations are initially mild and that oral or genitourinary mucocutaneous lesions precede possible severe involvement. Male gender, younger age of onset and greater number of organs involved in the diagnosis are associated with a more severe disease and require more aggressive treatment. Conclusion: The early diagnosis of Behcet's Disease is challenging due to the plurality of symptoms which are also similar in several autoimmune pathologies. In cases of less severe manifestations, the use of steroids and/or immunosuppressants may be sufficient for disease remission.